IVF outcome in azoospermic cancer survivors. (January 2018) - Dar, S.; Orvieto, R.; Levron, J.; Haas, J.; Gat, Itai; Raviv, G.
Abstract: Objective: To assess clinical outcome among infertile couples treated by in vitro fertilization (IVF) and intra cytoplasmic sperm injection (ICSI) using testicular sperm from azoospermic cancer survivors. Study design: This clinical retrospective study included infertile couples treated in a single tertiary referral center between 1996 and 2013. All male partners were cancer survivors who were diagnosed with azoospermia due to previous gonadotoxic treatments and referred to testicular sperm extraction (TESE). Retrieved sperm was used for IVF-ICSI among patients' spouses. Sperm retrieval rate and IVF-ICSI outcome were evaluated. Results: Sperm was successfully retrieved in 12 out of 36 patients (33.3%) on initial TESE, with an overall sperm retrieval rate of 38.6% (17 of 44). Female patients were 29.8 ± 5.1 years old. The average number of retrieved oocytes was 14.0 ± 4.0 per cycle, with clinical pregnancy and live birth rates per successful TESE of 64% (11 of 17) and 58.8% (10 of 17), respectively. Age, serum FSH, testicular volume and time from chemotherapy to TESE were not significantly different between patients with successful TESE to those without. Patients suffering from seminomas had significantly higher sperm retrieval rate, as compared to patients who had Hodgkin's lymphoma (P = 0.024). Conclusions: Post-chemotherapy azoospermia can be successfully treated with TESE and ICSI, and should be offered to azoospermic cancer survivors who did not cryopreserve sperm prior to their gonadotoxic treatments.